Association of circulating nutritional markers, diets, lifestyle, workplace and environmental exposures with nasopharyngeal carcinoma in two public hospitals in Malaysia - Ulaganathan, Vaidehi (2018)
Malaysia is one of the Asian countries with a high incidence of nasopharyngeal carcinoma (NPC) with age-specific incidence rate (ASIR) of 7.2 per 100,000 population. Nutritional factors as well as workplace and environmental exposures have been implicated as risk factors of NPC. This case-control study was conducted to determine the association between circulating nutritional markers, diet, lifestyle factors, workplace and environmental exposure with risk and survival of NPC in the search for markers to predict risk and prognosticate survival for this disease. A total of 300 histologically confirmed NPC cases and 300 matched (age, gender, ethnicity) cancer-free controls from two local hospitals were recruited from 2012 to 2016. An interviewer-administrated questionnaire was used to capture information on sociodemographic background, dietary intake, physical activity, smoking, alcohol consumption and workplace and environmental exposures. Anthropometry measurements were taken directly after interview. The fasting blood sample was collected by a trained and qualified paramedic from respective hospitals and analyzed using relevant analysis in the laboratory. Clinical characteristics were obtained from patients’ medical records. The overall survival of NPC was 63.7% with 79.3% complete remission. Vigorous physical activity (AOR = 1.58, 95% CI = 1.09, 2.31), ex-smoking habit (AOR (quitted ≤ 2 years) = 4.69, 95% CI = 1.63, 13.5) and alcohol consumption (AOR (once a week) = 3.10, 95% CI =1.22, 7.91) significantly increased the risk of NPC. A medium consumption of high-protein dietary pattern was protective against NPC risk (AOR (Q2 vs Q1) = 0.44, 95% CI = 0.25, 0.76), while a high consumption of high-salted and processed food dietary pattern increased the risk of NPC (AOR (Q4 vs. Q1) = 9.75, 95% CI = 4.66, 20.38). Consumption of high vegetables and fruits dietary pattern showed no association with risk of NPC. Workplace exposures to leather, cloth, textiles or carpet (AOR (≥ 5 days/week) = 12.03, 95% CI = 1.39, 104.4) and dust, smoke, fumes or gases (AOR (≥ 5 days/week) = 2.50, 95% CI = 1.54, 4.07) significantly increased the risk of NPC. Environmental exposure to disinfectants or biocides significantly increased the risk of NPC (AOR = 2.84, 95% CI =1.21, 6.68). Advanced NPC stage (AOR (Stage 4C) = 5.64, 95% CI =1.13, 28.2), treatment with chemotherapy alone (AOR = 5.58, 95% CI = 2.30, 13.50) and low serum leptin level (AOR (Q1 vs. Q4) = 9.61, 95% CI = 3.36, 27.47) significantly increased risk of NPC mortality. In conclusion, the generation of risk models in this study based on these factors would not only increase understanding of NPC aetiology, but could potentially contribute to planning and implementation of clinical and public health interventions.